Management of a hopeless mandibular molar: A case report - asgary, saeed (Iranian Endodontic Journal, 2011)
<span style="font-family: ";Times New Roman";,";serif";; color: black; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-language: EN-US; mso-ansi-language: EN-GB;" lang="EN-GB">Intentional tooth reimplantation can be an alternative treatment option for teeth with poor or hopeless prognosis where coronal and surgical endodontic treatment(s) are not possible. This technique may help to restore a natural tooth to function in preference to prosthesis/implant replacements. A 38-years old male was referred to private practice with persistent chronic apical periodontitis of a previously root canal treated mandibular left first molar. A furcal perforation and distolingual cusp fracture was previously repaired and treated with amalgam (~5 years ago). In view of the patient/tooth’s limitations, intentional reimplantation was planned using CEM cement retrograde filling. Clinical and radiographic follow-up during 2 years postoperatively revealed no sign/symptoms of infection or inflammation. Moreover, periradicular healing was evident on radiographs.